QS6: Developing The Psychosocial Growth Chart. (July 2021) - Huang, Kelly X.; Hu, Vivian J.; Oberoi, Michelle K; Caprini, Rachel M.; Patel, Harsh; Lee, Justine C.
Abstract : Background: While improvement in quality of life has long been the ultimate goal in the care of children born with craniofacial anomalies, the intersection between surgical care and psychosocial functioning has not been well understood. A major reason for this discrepancy is the lack of consistent, systematic, validated, and quantitative assessments of psychosocial functioning incorporated as standard of care. Traditional screening within multi-disciplinary teams has relied upon qualitative evaluations by pediatricians, social workers, and psychologists. However, qualitative exams do not allow for the comparison of psychosocial outcomes accurately over time. One of the first steps in establishing psychosocial functioning as a measured health outcome in children with craniofacial anomalies is to chart their typical psychosocial development longitudinally. Our group previously reported that children with craniofacial anomalies are at increased risk for psychosocial dysfunction from ages 8-10 in a cross-sectional analysis. In this work, we evaluate the longitudinal changes over 5 years of the original cohort of children between ages 8-10 as an initial pilot study to develop a psychosocial growth chart for children with craniofacial anomalies. Methods: From 2015 to 2020, children with craniofacial anomalies from the University of California Los Angeles were prospectively evaluated using the Pediatric Patient-Reported Outcomes Measurement Information System to assess anger, anxiety, depression, and peer relationships. Demographics and patient characteristics were also recorded. Changes in psychosocial functioning from ages 8-14 were evaluated using linear regression analyses, and responses at ages 8-10 were compared to responses at ages 11-14 using paired samples t tests. Results: Overall, 29 patients were assessed longitudinally yielding a total of 97 data points (3.34 ± 1.45 per patient), of which 23 patients were surveyed at both ages 8-10 and ages 11-14 yielding 87 data points (3.78 ± 1.24 per patient). Primary diagnosis included cleft lip and/or palate (n = 13), microsomia (n = 6), and others (n = 10). There was a decreasing linear trend from ages 8-14 for anger, anxiety, and depression among all 29 patients. In particular, increasing age was a significant negative predictor of anger (β = -0.25, p = 0.01). Psychosocial functioning improved overall when comparing the responses from ages 8-10 to ages 11-14 among the 23 patients, as characterized by trends of decreased anger, anxiety, and depression and improved peer relationships. In subset analysis, children with cleft lip and/or palate reported significantly higher anxiety symptoms at ages 8-10 (52.1 ± 9.7) than at ages 11-14 (47.1 ± 9.5, p = 0.02). No differences in psychosocial functioning were found when patients were stratified by insurance type, family language, ethnicity, or sex. Conclusions: The current longitudinal study of psychosocial functioning in children with craniofacial anomalies demonstrates age-related changes in concordance with our previous cross-sectional work. The current study serves as the initial pilot study for developing a psychosocial growth chart for children with craniofacial anomalies that may be incorporated as standard of clinical care. Future directions include expansion of longitudinal analyses with potential stratification based on diagnostic subsets and evaluation of children without medical diagnoses for comparison.